Impact of “COVID-19” on the Life of Destitute People: A Soft-Measurement in Bangladesh - Shuvro, Razuan Ahmed; Talukder, Md. Mohosin (Bangladesh Journal of Multidisciplinary Scientific Research, 2020)
The world has been crippling due to COVID 19. This pandemic has affected the lives of everyone. But the people who belong to the lower ladder in socioeconomic status may suffer more due to COVID 19 in developing countries. This paper aimed to explore factors influenced by COVID 19 and their association with the impact of COVID 19 on the life of destitute people. To reach the aim, the authors adopted a quantitative approach. A field survey on a sample of 250 destitute people was conducted using a self-constructed questionnaire. Factor analysis (principle component) found that 5 factors are influenced by COVID 19 in the life of destitute people and these are mental trauma and fear, full of uncertainty, reduced income level, feeling helplessness, and health safety issues. With a composite mean of 3.4056 and 0.698 standard deviations often tangible and intangible aspects of life, the paper found a moderate negative impact of COVID 19 on the life of destitute people. Multiple regression analysis evinces that factors found in factor analysis can explain 67.2% variance and has a statistically significant association with the impact of COVID 19 on the life of destitute people and among the five factors mental trauma and fear are the most influential (β.279, P< 0.05). Finally, this paper concluded that cogitation of factors found in this paper may help the authority to mitigate the negative impact of such pandemic on the life of destitute people in a developing country like Bangladesh.